2021
DOI: 10.1111/kykl.12282
|View full text |Cite
|
Sign up to set email alerts
|

Labor market effects of COVID‐19 in Sweden and its neighbors: Evidence from administrative data

Abstract: This paper studies the labor market effects of non‐pharmaceutical interventions (NPIs) to combat the COVID‐19 pandemic. We focus on the Nordic countries which showed one of the highest variations in NPIs despite having similar community spread of COVID‐19 at the onset of the pandemic: While Denmark, Finland and Norway imposed strict measures (‘lockdowns’), Sweden decided for much lighter restrictions. Empirically, we use novel administrative data on weekly new unemployment and furlough spells from all 56 regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…From Figure 6 , there is no significant difference in the pattern of stock prices in Sweden from January 2020 to July 2021 relative to the stock price pattern in other Nordic countries in the same timeframe. A Nordic (Denmark, Finland, Norway, and Sweden) labour market study up to week 21 (mid-May) of 2020 showed that the labour markets were severely affected, with the Swedish labour market being impacted by a time lag of 2-3 weeks compared to its neighbours, and the cumulative sum of new unemployment and furlough spells for Sweden remaining significantly lower [ 16 ]. However, the cumulative sum of new unemployment and furlough spells of Denmark, Finland, and Norway all showed a decreasing trend when compared to Sweden at week 21 (mid-May) of 2020 and would have likely shown an insignificant result had it continued for the entire time span of our study, until the end of 2020 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 6 , there is no significant difference in the pattern of stock prices in Sweden from January 2020 to July 2021 relative to the stock price pattern in other Nordic countries in the same timeframe. A Nordic (Denmark, Finland, Norway, and Sweden) labour market study up to week 21 (mid-May) of 2020 showed that the labour markets were severely affected, with the Swedish labour market being impacted by a time lag of 2-3 weeks compared to its neighbours, and the cumulative sum of new unemployment and furlough spells for Sweden remaining significantly lower [ 16 ]. However, the cumulative sum of new unemployment and furlough spells of Denmark, Finland, and Norway all showed a decreasing trend when compared to Sweden at week 21 (mid-May) of 2020 and would have likely shown an insignificant result had it continued for the entire time span of our study, until the end of 2020 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Norway, Denmark, and Finland had strict measures with lockdowns, border controls and quarantine, as early as March 2020 [15][16][17]. Iceland did not have a lockdown, but instead relied on an aggressive strategy of mass-testing, contact tracing, quarantine, and isolation [18] Denmark's response was to "Act fast and act with force"; mitigation measures were implemented, and testing capacity was increased nationwide as a preventive strategy to decrease transmission [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…( 2020 ), Juranek et al. ( 2021 ) and Gupta et al. ( 2020 ) provide empirical evidence that this pandemic has resulted in large employment losses and substantial declines in hours worked.…”
Section: Literaturementioning
confidence: 99%
“…Social distancing measures can be an effective policy response to stages of exponential growth of SARS-CoV-2 contagion ( [2] , [3] , [4] , [5] , [6] ). However, they come at the cost of tremendous economic losses ( [7] , [8] , [9] ), jeopardize civil liberties ( [10] , [11] ), require the introduction of new sanctions [12] , [13] and threaten incumbent governments’ popularity (14) . The pandemic forces policymakers to face difficult trade-offs, not only in economic and public health terms but also regarding consensus.…”
Section: Introductionmentioning
confidence: 99%